A combined theoretical and experimental study of the ultrafast photophysics of Rhodamine B. (2nd September 2018) - Catone, Daniele; O'Keeffe, Patrick; Satta, Mauro; Paladini, Alessandra; Ciavardini, Alessandra; Toschi, Francesco; Turchini, Stefano; Avaldi, Lorenzo
ABSTRACT: The ultrafast dynamics of zwitterionic and cationic Rhodamine B in ethanol have been investigated using TDDFT calculations and ultrafast transient absorption spectroscopy. The calculations show that the zwitterionic form exhibits an electronically excited dark state which could potentially quench the initially photoexcited state, while in the case of cationic form the lowest excited lying dark state is outside the energy region of interest and cannot explain its quenching. Due to similarities in the relaxation dynamics of the two molecules, it is suggested that the electronically excited dark state may not play such an important role in the quenching process of this dye as previously proposed. Experimental evidence presented suggests that a quenching mechanism is active on the picosecond timescale for both forms of Rhodamine B. Abstract :